Persetujuan Perkawinan Atas Sukut (Diam) Perempuan Ketika Peminangan Dalam Pandangan Hukum Di Indonesia - Argadinata, Frandy (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
Engagement is the first step taken by someone when they are about to get marriage. In this engagement, individuals are encourage to get to know each other (ta’aruf). This statement emphasize the emportance of transparency and communication between individuals during the engagement process to facilitate a smooth relationship in the future family life. This research examines the concept of “sukut” (silence) as a form concent for women in marriage proposals in Indonesia, particularly under Islamic law. It critiques the legal framework that interprets a woman’s silence as consent, which can perpetuate gender inequality and marginalize women’s voice in marital decisions. The study emphasizes the necessity of mutual consent in marriage, as mandated by Indonesian laws and Islamic law (fiqh), and highlights the risk of coercion when a woman’s silence is misinterpreted. The research employs a literature review methodology to analize these issues and suggests improvements for legal protections of women’s rights in marriage. The conclusion of this research is that marriage conducted without the explicit consent of each party, especially the bride, can lead to forced marriages. And forced marriage is fundamentally contrary to the principles of marriage in Islam and the legal regulations regarding sexual violence.